Effect of endogenous sodium and potassium ions in plants on the quality of alfalfa silage and bacterial community stability during fermentation - Shi, Jinhong; Zhang, Guijie; Ke, Wencan; Pan, Yongxiang; Hou, Meiling; Chang, Chun; Sa, Duowen; Lv, Mingju; Liu, Yinghao; Lu, Qiang (Frontiers in Plant Science, 2023)
This study investigated the impact of endogenous sodium and potassium ions in plants on the quality of alfalfa silage, as well as the stability of bacterial communities during fermentation. Silage was produced from the fermented alfalfa, and the chemical composition, fermentation characteristics, and microbiome were analyzed to understand their interplay and impact on silage fermentation quality. The alfalfa was cultivated under salt stress with the following: (a) soil content of ＜ 1‰ (CK); (b) 1‰-2‰ (LP); (c) 2‰-3‰ (MP); (d) 3‰-4‰ (HP). The results revealed that the pH of silage was negatively correlated with the lactic acid content. With the increase of lactic acid (LA) content increased (26.3 ~51.0 g/kg DM), the pH value decreased (4.9 ~5.3). With the increase of salt stress, the content of Na + in silage increased (2.2-5.4 g/kg DM). The presence of endogenous Na + and K + ions in plants significantly affected the quality of alfalfa silage and the dynamics of bacterial communities during fermentation. Increased salt stress led to changes in microbial composition, with Lactococcus and Pantoea showing a gradual increase in abundance, especially under high salt stress. Low pH inhibited the growth of certain bacterial genera, such as Pantoea and Pediococcus. The abundance of Escherichia-Shigella and Comamonas negatively correlated with crude protein (CP) content, while Enterococcus andLactococcus exhibited a positive correlation. Furthermore, the accumulation of endogenous Na + in alfalfa under salt stress suppressed bacterial proliferation, thereby reducing protein degradation during fermentation. The pH of the silage was high, and the LA content was also high. Silages from alfalfa under higher salt stress had higher Na + content. The alpha diversity of bacterial communities in alfalfa silages showed distinct patterns. Desirable genera like Lactococcus and Lactobacillus predominated in silages produced from alfalfa under salt stress, resulting in better fermentation quality.